Produção, caracterização, estabilidade e aplicação de microcapsulas de licopeno - Rocha-Selmi, Glaucia Aguiar, 1984- (2009)
Orientadores: Carlos Raimundo Ferreira Grosso, Carmen Silvia Favaro Trindade